Pengaruh Peer Teaching Terhadap Peningkatan Keterampilan CPR (Cardiopulmunary Resuscitation) Pada Siswa SMA 7 Tasikmalaya - Yeli Yulianti; Dandi Oka Subantara; Teti Agustin (Universitas Galuh, 2026)
Sudden cardiac arrest is one of the leading causes of death worldwide and requires immediate bystander intervention through Cardiopulmonary Resuscitation (CPR). However, CPR skills among high school students remain suboptimal. Peer teaching has been identified as an effective learning strategy to enhance psychomotor skills through peer-based interaction. This study aimed to examine the effect of peer teaching on improving CPR skills among students at SMA Negeri 7 Tasikmalaya. A quantitative pre-experimental one-group pretest–posttest design was employed involving 38 tenth-grade students selected using purposive sampling. CPR skills were assessed using a checklist based on the American Heart Association (AHA) 2020 guidelines. Data were analyzed using the Shapiro–Wilk normality test and paired t-test. The results demonstrated a significant increase in posttest CPR skill scores compared to pretest scores (p < 0.001), with a very large effect size (Cohen’s d = 1.98). In conclusion, peer teaching is highly effective in improving CPR skills among high school students.